2022
DOI: 10.3390/ijms231911560
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metagenomics and Metabolomes Reveals Abnormal Metabolism Activity Is Associated with Gut Microbiota in Alzheimer’s Disease Mice

Abstract: A common symptom in Alzheimer’s disease (AD) is cognitive decline, of which the potential pathogenesis remains unclear. In order to understand the mechanism of gut microbiota in AD, it is necessary to clarify the relationship between gut microbiota and metabolites. Behavioral tests, pathological examination, metagenomics, and metabolomics were applied to analyze the difference of gut microbiota and metabolome between APPswe/PS1ΔE9 (PAP) mice with cognitive decline and age-matched controls, and their possible c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The intestinal abundance of Dub has been reported to be associated with obesity 42 and Alzheimer’s disease 43 in mouse models, however no functional studies have been performed to confirm its biological relevance in vivo. For the very first time, we comprehensively analyzed its potential role as a probiotic in both conventional and microbiota-depleted mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal abundance of Dub has been reported to be associated with obesity 42 and Alzheimer’s disease 43 in mouse models, however no functional studies have been performed to confirm its biological relevance in vivo. For the very first time, we comprehensively analyzed its potential role as a probiotic in both conventional and microbiota-depleted mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Both in Alzheimer's disease and mice with SOD1 knockout as a model of aging, we observed a significant increase in the abundance of P. clara. 60,61 Jongoh Shin and colleagues demonstrated that Paraprevotella, a bacterial species positively associated with age-related changes, exhibits a significantly increased abundance in aging mice. However, when A. muciniphila was reintroduced to the aging mice, phenotypic improvements were observed, and the abundance of Paraprevotella decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, a significantly decreased abundance of bacteria belonging to the Clostridia_UCG-014 family has been documented in relation to increased cognitive frailty index scores [ 53 ]. Notably, the abundance of both Turicibacter and Dubosiella genera was also decreased in APP swe /PS1 ΔE9 mice [ 54 ].…”
Section: Discussionmentioning
confidence: 99%